Geothermal properties of the ground in Cyprus and their effect on the efficiency of ground coupled heat pumps - Florides, Georgios A.; Pouloupatis, Panayiotis; Kalogirou, Soteris A.; Messaritis, Vassilios; Panayides, Ioannis; Zomeni, Zomenia; Partasides, George; Lizides, Andreas; Sophocleous, Eleni; Koutsoumpas, Kostas (My University, 2013)
A Project funded by the Research Promotion Foundation of Cyprus was undertaken by the Cyprus University of Technology and other collaborators, to investigate and determine the geothermal parameters of the ground in Cyprus since such information is currently unavailable. The purpose of this paper is to report on the ground temperatures collected by now, at the six representative sites in relation to depth, time of the year, structure of the ground and altitude and report on their impact on the efficiency of Ground Coupled Heat Pumps. Every month since October 2009, the temperature of the ground is being recorded along the depth of the boreholes. It is anticipated that the project will be completed by the end of 2010 and geothermal information will be collected and reported for all six locations. The data collected until now clearly indicate that there is a potential for the efficient use of GCHPs in Cyprus leading to significant savings in power.
Keywords: Geothermal; Ground temperatures; Heat pump efficiency; Ground heat exchangers